Thermodinamically stable phases in the CaO-SiO2-Al2O3-CaSO4-H2O closed system at 25 ºC. Application to cementitious systems - Martínez-Ramírez, S.; Blanco-Varela, M. T. (Materiales de Construcción, 2009)
One of the chief causes of cement and concrete deterioration is the loss of durability prompted by sulphate attack. The existing standards call for long test periods (2- 12 months). Thermodynamic modelling is a particularly appropriate technique for studying systems that only reach equilibrium in the long term. Used in the present study to establish the fields of thermodynamic stability for the phases in the CaO-SiO2-Al2O3-CaSO4-H2O system at 25 ºC. According to the model, gypsum is stable at sulphate ion concentrations of 1.23e-2 mol/kg and over, while ettringite exhibits stability at concentrations ranging from 7.64e-6 to 1.54e-2 mol/kg. Ettringite is compatible with all system phases except SH and gypsum only with ettringite, the C-S-H gels, AH3 and SH. None of the calcium aluminates or silicoaluminates in the system is compatible with gypsum: in its presence, they all decompose to cement deteriorating ettringite. Finally, the model revealed that the maximum sulphate concentration at which C-S-H gel is stable is slightly higher in systems with than without Al2O3.